2022-RA-1219-ESGO Succor quality: validation of ESGO quality indicators for surgical treatment of cervical cancer. (20th October 2022) - Boria, Felix; Martin-Calvo, Nerea; Chacón, Enrique; Berasaluce, Arantxa; Manzour, Nabil; Vazquez, Daniel; Castellanos, Teresa; Chiva, Luis
Abstract : Introduction/Background: The main objective of this study was was to evaluate the impact in the disease-free survival and risk of relapse of ESGO quality indicators compliance in cervical cancer surgery. Methodology: In this retrospective cohort study 15 ESGO quality indicators were assessed in the succor database (patients who underwent radical hysterectomy for stage IB1 cervical cancer (FIGO 2009)), and the final score ranged between 0 and 16 points. Centers with more than 13 points were classified as high-quality indicator compliance centers. We constructed a weighted cohort using inverse probability weighting to adjust for the variables and using inverse probability weighting. We compared disease-free survival and overall survival using Cox proportional hazards regression analysis in the weighted cohort. Results: A total of 838 patients were included in the study. The mean number of quality indicators compliance in this cohort was 13.6 (SD 1.45). 479 patients were operated in high compliance centers and 359 patients were operated in low compliance centers. Women who were operated on centers with high compliance of quality indicators had significant lower risk of relapse (HR, 0.39; 95% CI, 0.25 to 0.61; P<0.001). The association was slightly reduced but remained significant after further adjustment for surgery related variables – conization, surgical approach and use of manipulator- (HR, 0.48; 95% CI, 0.30 to 0.75; P=0.001) and variables related with clinical evolution- Adjuvant therapy- (HR, 0.47; 95% CI, 0.30 to 0.74; P=0.001). Risk of death from the disease was significantly lower in women operated on in centers with high adherence to quality indicators (HR, 0.42; 95% CI, 0.19 to 0.97; P=0.041). However, the association became no significant after the adjustment for surgery and clinical related variables. Conclusion: Patients with early-stage cervical cancer operated on centers with high compliance of ESGO quality indicators have lower risk of recurrence and death.